1977
DOI: 10.1084/jem.146.5.1169
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutination by purified type I Escherichia coli pili.

Abstract: Many enterobacteria can cause agglutination of erythrocytes, but previous investigations have not proven which components of the bacteria are responsible. We used a strain of Escherichia coli K12 which causes mannose-sensitive hemagglutination (HA) of guinea pig cells. Common pili were purified from these bacteria by shearing them from the bacteria followed by selective precipitation in acid and ammonium sulfate. Isopycnic centrifugation in cesium chloride removed the remaining outer membrane protein contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
239
1

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(251 citation statements)
references
References 29 publications
11
239
1
Order By: Relevance
“…However, for this to be true, FimH presented at the fimbrial tip as well as FimH intercalated along the shaft would both have to be able to mediate adhesion. Much previous work has indicated that only FimH present at the tips of fimbriae is functional in mediating adhesion (35,(45)(46)(47)(48). For example, type 1 fimbriae have been observed to bind to erythrocyte membranes as well as the uroepithelium by the tips of the fimbriae (46,49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for this to be true, FimH presented at the fimbrial tip as well as FimH intercalated along the shaft would both have to be able to mediate adhesion. Much previous work has indicated that only FimH present at the tips of fimbriae is functional in mediating adhesion (35,(45)(46)(47)(48). For example, type 1 fimbriae have been observed to bind to erythrocyte membranes as well as the uroepithelium by the tips of the fimbriae (46,49).…”
Section: Discussionmentioning
confidence: 99%
“…For example, type 1 fimbriae have been observed to bind to erythrocyte membranes as well as the uroepithelium by the tips of the fimbriae (46,49). In addition, non-aggregated cell-free type 1 fimbriae do not agglutinate erythrocytes, whereas aggregated type 1 fimbriae and whole bacteria both cause hemagglutination (45,46,48), strongly indicating that, with respect to adhesion, type 1 fimbriae are monovalent. The work of Ponniah et al (47) supports this idea by showing that fragmentation of type 1 fimbriae greatly increases their mannose-binding activity by exposing FimH that was previously intercalated into the fimbrial shaft, indicating that shaft-located FimH is not functional in adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation and purification of type 1 pili. This was performed essentially according to the procedure described by Salit and Gotschlich (17). The strains 301 or 501, which expressed only type 1 pili were used.…”
Section: Methodsmentioning
confidence: 99%
“…A number of bacterial pili have been established as having lectin-like properties, including type IV pili of P. aeruginosa, which bind to ␤GalNAc(1-4)␤Gal of glycosphingolipids Sheth et al, 1994), the type 1 fimbriae of Escherichia coli, which bind to mannose residues (Salit and Gotschlich, 1977;Rivier and Darekar, 1975), and the E. coli pap-pili with binding specificity to ␣Gal(1-4)␤ disaccharides (Bock et al, 1985). We have previously investigated the nature of the gonococcal host cell receptor and found that the pilus-mediated attachment of the bacteria to human tissue is mediated by a eukaryotic receptor with protein characteristics (Jonsson et al, 1994).…”
Section: Introductionmentioning
confidence: 99%